Assessment of readiness for implement the Circular 15/2015/TT-BYT on health insurance for HIV patients in Dak Lak province, 2017 - Nguyễn Thúy, Quỳnh; Nguyễn Thanh, Hà (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2018)
Nguyen Duc Thanh1*, Le Dinh Vinh2, Bui Thi My Anh1, Chu Huyen Xiem11Hanoi University of Public Health2Dak Lak Center for HIV/AIDS prevention Objectives: describe the readiness and analyse barriers to implement Circular 15/2015/TT-BYT.Methods: A cross-section study combined quantitative and qualitative research was conducted by 142 interviews of patients receiving ARV treatment at 03 OPCs, 07 in-depth interviews and 04 group discussions in DakLak province in 2017.Main findings: the management, implementation and service provision groups have made preparations for the implementation of Circular 15/2015/TT-BYT through various measures like increasing health insurance rate, ensuring benefts for patients. In this group, the biggest obstacle was strengthening of HIV/AIDS prevention centre so that they had enough facilities and human resources to sign health insurance contracts with Social insurance Agency. For the benefciaries - HIV/AIDS patients, they need more impact to increase the proportion of health insurance from 42.3% to over 70% as orientation. For the benefciaries - HIV/AIDS patients, they need more impact to increase the proportion of health insurance from 42.3% to over 70% as orientation. This group also encountered many barriers that prevent patients from buying and using health insurance, such as having no money to buy and pay for health insurance, limited knowledge of health insurance with 55% of respondents not qualifed and the biggest obstacle is still stigma and discrimination with HIV/AIDS.Conclusions: to improve readiness of The Circular 15/2015/TT-BYT implementation, the leaders and managers should implement measures to promote health insurance information, reduce stigma and strengthen policies to support patients to buy health insurance.Keywords: health insurance, HIV/AIDS patient. *Corresponding author: Nguyen Duc ThanhWork place: Hanoi University of Public HealthEmail: ndt@huph.edu.vn